Selected microbial groups and short-chain fatty acids profile in a simulated chicken cecum supplemented with two strains of Lactobacillus. - A., Meimandipour; Mustafa, Shuhaimi; A. F., Soleimani; Kasim, Azhar; Bejo, Mohd Hair; B. M., Kabeir; A., Javanmard; Othaman, Muhammad Anas; Abdul Manap, Mohd Yazid (2010)
Among the bacterial fermentation end products in the chicken cecum, butyrate is of particular importance because of its nutritional properties for the epithelial cell and pathogen inhibitory effects in the gut. An in vitro experiment, operated with batch bioreactor, was conducted to quantify butyric-producing bacteria in a simulated broiler cecum supplemented with Lactobacillus salivarius ssp. salicinius JCM 1230 and Lactobacillus agilis JCM 1048 during 24 h of incubation. Selected bacterial species were determined by real-time PCR and short-chain fatty acids and lactate concentrations were monitored. The results showed that after 24 h of incubation, Lactobacillus supplementation significantly increased the number of lactobacilli, bifidobacteria and Faecalibacterium prausnitzii in medium containing cecal content and lactobacilli supple-mentation (Cc + L) compared with the control (Cc). Addition of lactobacilli did not alter Escherichia coli and Clostridium butyricum, whereas it significantly (P < 0.05) reduced Salmonella in treatment Cc + L compared with the Cc treatment. Propionate and butyrate formation were significantly (P < 0.05) increased in treatment Cc + L as compared with the Cc treatment. Lactate was only detected in treatment containing 2 Lactobacillus strains. After 24 h of incubation, acetate concentration significantly (P < 0.05) decreased in all treatments. It was suggested that lactate produced by Lactobacillus in the cecal content improved the growth of butyric producers such as F. prausnitzii, which significantly increased butyrate accumulation. Additionally, the results showed that butyrate and propionate inhibited Salmonella without influencing the E. coli profile.